Penerapan Problem Based Learning Berbantuan LKPD Berbasis Sumber Daya Alam untuk Meningkatkan Berpikir Kritis peserta didik Kelas VIII di SMP Negeri 1 Bangil - Syahidin, Muhammad; Hari Purnomo, Nugroho; Muzayanah, Muzayanah (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2025)
This study aims to examine the application of the Problem Based Learning (PBL) method assisted by the Natural Resources-based Learner Worksheet (LKPD) in improving the critical thinking skills of class VIII students at SMP Negeri 1 Bangil. The background of this study is based on the low critical thinking skills of students in conventional learning which is more oriented towards memorization. The PBL method was chosen because it is learner-centered and involves them in solving real problems that are relevant to everyday life, so that it can encourage the development of critical thinking contextually. This study used a quantitative approach with a pretest-posttest design in the experimental group. The sample consisted of students of VIII A and VIII B classes totaling 61 people who were randomly selected. The results showed that there was an increase in the “Very Critical” category, experimental class students increased from 3 students (10%) in the pre-test to 8 students (26.7%) in the post-test. In the “Critical” category, students increased from 4 students (13.3%) in the pre-test to 9 students (30%) in the post-test. Thus, this study is expected to contribute to the development of learning models that focus on critical thinking skills in junior high schools, as well as a reference for educators in improving the quality of relevant and problem-based learning.